2010
DOI: 10.1007/s11695-010-0073-7
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes, Satiety, and Adverse Upper Gastrointestinal Symptoms Following Laparoscopic Adjustable Gastric Banding

Abstract: Patients are highly satisfied with the outcome of LAGB and achieve substantial weight after 3 years. Expected ranges of satiety, adverse symptoms, and outcomes have been defined. The most troublesome symptom is the inability to consume certain foods. Weight loss predicted overall satisfaction, regardless of adverse symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
25
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 18 publications
4
25
1
Order By: Relevance
“…The introduction of more modern bands adapted to the laparoscopic approach and the implementation of a more prudent strategy for postoperative band adjustments, might have permitted a reduction in vomiting frequency after surgery. However, in a recent cross-sectional analysis of 323 patients treated with LAGB from 2003 to 2007, Burton et al [24] reported 9% of patients with daily food regurgitation and an additional 23% of patients having regurgitation more frequently than once per week. The inability to consume a range of foods because of the regurgitation was cited in their study as the most troublesome symptom or problem after surgery by 66% of patients [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The introduction of more modern bands adapted to the laparoscopic approach and the implementation of a more prudent strategy for postoperative band adjustments, might have permitted a reduction in vomiting frequency after surgery. However, in a recent cross-sectional analysis of 323 patients treated with LAGB from 2003 to 2007, Burton et al [24] reported 9% of patients with daily food regurgitation and an additional 23% of patients having regurgitation more frequently than once per week. The inability to consume a range of foods because of the regurgitation was cited in their study as the most troublesome symptom or problem after surgery by 66% of patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…The entity of the improvement in HRQOL observed after LAGB might be only partly explained by the degree of weight loss [7,10,11], and it might also be influenced by preoperative co-morbidities [7] and the interval after surgery [10]. However, LAGB can also cause adverse upper gastrointestinal side effects in some patients [24]. The relative weight of these symptoms (an inability to consume solid foods, moderate dysphagia, occasional regurgitation) on overall patient satisfaction has been reported to be low in a cross-sectional analysis of obese subjects treated with LAGB [24].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Even stable, successful patients do at times regurgitate foods of an inappropriate bolus consistency. 18 Although these mechanical realities are imposed by the LAGB, whether they are central to the behavioral adaptations, and consequent weight loss remains unclear.…”
Section: Mode Of Weight Loss With Lagbmentioning
confidence: 99%
“…24 Burton studied the mechanism of action of the adjustable gastric band, which is considered the model of the restrictive principle. [25][26][27][28][29][30][31] He has accomplished detailed manometric and transit studies to reveal that the band is not restrictive in the sense commonly understood, but may rather induce diminished nutrient intake and weight loss for other reasons.…”
mentioning
confidence: 99%